2007
DOI: 10.1021/ja067487h
|View full text |Cite
|
Sign up to set email alerts
|

Pentaindenocorannulene and Tetraindenocorannulene:  New Aromatic Hydrocarbon π Systems with Curvatures Surpassing That of C60

Abstract: It gives us great pleasure to report syntheses and X-ray crystal structures of two new geodesic polyarenes, pentaindenocorannulene 1 (1, C 50 H 20 ) and tetraindenocorannulene 2 (2, C 44 H 18 ) (Figure 1). These extended aromatic π systems constitute the largest curved subunits of C 60 ever prepared. 3 In agreement with theoretical predictions, the trigonal carbon atoms at the cores of these new hydrocarbons suffer even greater pyramidalization than that exhibited by the carbon atoms of C 60 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
141
1
2

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(146 citation statements)
references
References 14 publications
2
141
1
2
Order By: Relevance
“…[5] Furthermore, the specially functionalized precursors can be converted to the desired nanostructures by mild liquid-phase methods such as Pd(0) catalyzed direct arylation. [10] Several buckybowl structures have been synthesized by this route, [11] but extension of this approach to fullerene syntheses seems to be difficult since the Pd catalyzed aryl-aryl coupling does not occur in a domino fashion. Recently, we have demonstrated fluorine functionalization as an alternative synthetic method to overcome the above mentioned limitations.…”
mentioning
confidence: 99%
“…[5] Furthermore, the specially functionalized precursors can be converted to the desired nanostructures by mild liquid-phase methods such as Pd(0) catalyzed direct arylation. [10] Several buckybowl structures have been synthesized by this route, [11] but extension of this approach to fullerene syntheses seems to be difficult since the Pd catalyzed aryl-aryl coupling does not occur in a domino fashion. Recently, we have demonstrated fluorine functionalization as an alternative synthetic method to overcome the above mentioned limitations.…”
mentioning
confidence: 99%
“…[39] More recently Scott and Petrukhina research groups reported the solution phase synthesis and structural characterization of the whole family of indenocorannulenes, comprising monoidenocorannulene (C 26 ). [40] The synthesis started with Suzuki-Miyaura coupling of (o-chlorophenyl)-boronic acid with halogenated corannulenes and the subsequent ring closures of the resulting (poly)-2-chlorophenylcorannulenes by the microwave-assisted palladium-catalyzed intramolecular arylations.…”
Section: Corannulene As a Starting Materials For Preparations Of Largementioning
confidence: 99%
“…In fact, in five of the seven indenocorannulenes the maximum pyramidalization of the carbon atoms exceeds that of the carbon atoms in C 60 . [40] In addition to their interesting structural properties indenocorannulenes like 42 may be considered as potential precursors for the synthesis of carbon nanotubes of uniform diameter. [40] …”
Section: Corannulene As a Starting Materials For Preparations Of Largementioning
confidence: 99%
See 1 more Smart Citation
“…Calixarenes [1,2] and resorcinarenes [1,3] in supramolecular chemistry are prominent examples, as well as fullerene fragments [4] in material science. During our ongoing studies on the synthesis and applications of pentaarylcyclopentadienes [5,6] we noticed that both hydrogenation and dehydrogenation of pentaarylcyclopentadienes 1 should lead to spherical structures with spatially adjusted functional groups.…”
Section: Introductionmentioning
confidence: 99%